Evaluasi Pelatihan Jarak Jauh Penyuluh Pajak Menggunakan Model Kirkpatrick dan Importance Performance Analysis - Agus Suharsono; Oscar Wibiyakto (Universitas Indraprasta PGRI Jakarta, 2021)
Basic Tax Extension Remote Training is a mandatory training to be appointed as a Tax Extension Functional Officer at the Directorate General of Taxes, which is a new functional position, the implementation of the training is also the first time conducted, and is carried out remotely due to the Covid-19 pandemic. The method used was the Kirkpatrick level-1 evaluation model and Importance Performance Analysis. The results of the level-1 evaluation of the implementation, all the elements evaluated were in quadrant I, meaning good and needed to be maintained. There were inputs to be considered in the implementation of the next training, namely the need to add learning videos on good communication, the need of application used in learning, reducing face-to-face meetings through zoom, and reducing hours of individual study in the evening. In Level-1 evaluation of the teachers, all elements of evaluation were included in quadrant I, meaning good and needed to be maintained. Currently, officials invited to give lectures are evaluated with the same instruments as the teachers. It is recommended that officials who give lectures are not evaluated as the teachers, because these officials are invited to lecture according to the authority of their position, not as teachers but as sources. Level-2 evaluation is very good because 96% of the participants passed with an excellent predicate.